2010
DOI: 10.1016/j.biortech.2008.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Development of a heavy metal sorption system through the P S functionalization of coconut (Cocos nucifera) fibers

Abstract: Lignocellulosic residues are interesting materials for the production of heavy metal adsorbents for aquatic systems. Whole fibers taken from coconut (Cocos nucifera) husks were functionalized with the thiophosphoryl (P=S) group by means of the direct reaction with Cl(3)PS, (CH(3)O)(2)ClP=S or (CH(3)CH(2)O)(2)ClP=S in order to obtain an adsorptive system for 'soft' metal ions, particularly Cd(2+). These functionalized fibers (FFs) were characterized by means of elemental analysis, infrared spectroscopy, thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…In order to obtain cheaper adsorbents, various lignocellulosics materials have been studied, including cellulosic substrates (Hubbe et al 2011), sugar cane bagasse Dos Santos et al 2011;Sanchez and Espósito 2011), cashew bagasse (Moreira et al 2009); coconut shell (Spinola et al 1999;Sousa et al 2007a, 2010b, 2011c., Bhatnagar et al 2010De Sousa et al 2010;Neto et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain cheaper adsorbents, various lignocellulosics materials have been studied, including cellulosic substrates (Hubbe et al 2011), sugar cane bagasse Dos Santos et al 2011;Sanchez and Espósito 2011), cashew bagasse (Moreira et al 2009); coconut shell (Spinola et al 1999;Sousa et al 2007a, 2010b, 2011c., Bhatnagar et al 2010De Sousa et al 2010;Neto et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This was further supported by comparing the values of R 2 ; the CFB experimental isotherm data had a higher R 2 for the Langmuir isotherm, which indicated the monolayer sorptions of Hg(II) onto the surface of CFB, with the maximum sorption capacities (q max ) for CFPristine and CF-NaOH of 166.67 and 142.86 mg=g, respectively. The applicability of the Langmuir isotherm model was also reported for the adsorption of Ni(II), Zn(II), and Fe(II) onto coconut fibers (Shukla et al, 2006) and Cd 2þ onto coconut fibers functionalized with thiophosphoryl (P = S) group (de Sousa et al, 2010). Hg(II) adsorption onto grafted poly(hydroxyethylmethacrylate) coconut coir pith fitted well into the Langmuir isotherm model (Anirudhan et al, 2007) and, in contrast to their earlier report, into the Freundlich isotherm model (Anirudhan et al, 2008).…”
Section: Cfb Sorption Isothermsmentioning
confidence: 85%
“…They found that the modified CF had a lower metal sorption capacity than unmodified CF. Other studies included the use of chemically modified and functionalized CF as biosorbents for the removal of heavy metal ions such as Ni(II), Zn(II), Fe(II), As(III), and Cd(II) (de Sousa et al, 2010;Shukla et al, 2006). In contrast to findings by Igwe et al (2008), their results indicated that modified CF possessed a higher sorption capacity than unmodified fiber (pristine) in adsorbing metal ions (Shukla et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…There are currently about a dozen models describing sorption of metal cations from aqueous media by cellulose-containing sorbents, with Langmuir theory being most commonly used by the authors [8,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%